2011
DOI: 10.1007/s00299-010-0987-5
|View full text |Cite
|
Sign up to set email alerts
|

The potential impact of plant biotechnology on the Millennium Development Goals

Abstract: The eight Millennium Development Goals (MDGs) are international development targets for the year 2015 that aim to achieve relative improvements in the standards of health, socioeconomic status and education in the world's poorest countries. Many of the challenges addressed by the MDGs reflect the direct or indirect consequences of subsistence agriculture in the developing world, and hence, plant biotechnology has an important role to play in helping to achieve MDG targets. In this opinion article, we discuss e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 63 publications
0
28
0
1
Order By: Relevance
“…Such aspects essentially need to be studied at individual or farm level. The many mentions of wellbeing in studies without farm-level data (37/48 studies) thus either relied on the limited number of empirically-based studies available or provided a more general discussion, or merely express future hopes or concerns, about potential wellbeing effects of GM crops (e.g., [49,54,79]). Eight of the 11 bottom-up studies connected wellbeing with empirically observed or farmers' experiences of effects on health.…”
Section: How Are Different Social Impacts Addressed?mentioning
confidence: 99%
“…Such aspects essentially need to be studied at individual or farm level. The many mentions of wellbeing in studies without farm-level data (37/48 studies) thus either relied on the limited number of empirically-based studies available or provided a more general discussion, or merely express future hopes or concerns, about potential wellbeing effects of GM crops (e.g., [49,54,79]). Eight of the 11 bottom-up studies connected wellbeing with empirically observed or farmers' experiences of effects on health.…”
Section: How Are Different Social Impacts Addressed?mentioning
confidence: 99%
“…merely shifting the challenge of micronutrient deficiency from one set of nutrients to another (2,18) .…”
Section: Introductionmentioning
confidence: 99%
“…Up to one-third of the world's population is currently at risk from vitamin deficiency disorders, which can have a severe impact on metabolism resulting in cumulative damage to health (1,2) . Strategies to address vitamin deficiency include the provision of supplements, the fortification of processed foods and the biofortification of crops to increase the vitamin content at source (3,4) .…”
Section: Introductionmentioning
confidence: 99%
“…The poverty-malnutrition-disease cycle needs to be broken by multipoint interventions that provide direct, effective and sustainable approaches to increase the economic welfare of the world's poorest people, including the provision of drugs and vaccines that tackle poor health, and adequate access to nutritious food (Perseley 2000). Although there are many global initiatives promoting short and mid-term strategies that tackle poverty, food insecurity/malnutrition and disease, we need sustainable solutions that provide the means for the world's poor to build their own healthy societies, as envisaged by the Millennium Development Goals (Yuan et al 2011).…”
Section: Introductionmentioning
confidence: 99%